simplify the equation to the form, which is simple to understand
-1/6(x-18)+1/2(x+2)=x+8
Simplifying:
-0.166666666667*(x-18)+1/2*(x+2)=x+8
Simplifying:
-0.166666666667*(x-18) + 0.5*(x+2)=x+8
Reorder the terms in parentheses
+(-0.166666666667x+3) + 0.5*(x+2)=x+8
Remove unnecessary parentheses
-0.166666666667x+3 + 0.5+*(+x+2+)=+x+8
Reorder the terms in parentheses
-0.166666666667x+3+( + 0.5x+1)=x+8
Remove unnecessary parentheses
-0.166666666667x+3 + 0.5x+1=+x+8
move all terms containing x to the left and all other terms to the right.
-0.166666666667x + 0.5x-1x=+8-3-1
simplify left and right side of the equation.
-0.666666666667x=+4
divide both sides of the equation by -0.666666666667 to get x.
x=-6
Hope I helped.